Adoção de inovações pela agricultura familiar: o caso do cultivo de uvas no estado de Goiás - FARIA, Sandra Santos (2012)
This study evaluated the ability of family farmers to adopt innovation. The example innovation chosen was the cultivation of grapes, which represent an ancient practice in some regions, but new to the family farmers of Goiás state. In an increasingly demanding market, the contemporary family farm seeks ways to innovate, either in the search for new markets, or in the production of novel products, is the use of technologies capable of improving the mode of production. To achieve the objectives proposed in this study, we sought methods (indicators) to evaluate the adaptability of farmers against the innovation (cultivation of grapes). These indicators assessed their ability to manage their activities and entrepreneurship (administrative indicators), to establish the vineyard according to the agronomic recommendations (agronomic indicators), to cover the costs for vineyard establishment (financial indicators) and also assess in which stage of the adoption process each farmer can be allocated in (stages of innovation indicator). The family farmers of Goiás state, with or without support from the government, as the technical or financial resources available to finance this new crop, did not intimidated themselves and faced challenges, expressing optimism for the coming years. It was found that most family farmers of Goiás state included in the survey are able to adopt this innovation.